Antiseizure Medication Withdrawal in Seizure-Free Patients: Practice Advisory Update Summary. (7th December 2021) - Gloss, David; Pargeon, Kimberly; Pack, Alison; Varma, Jay; French, Jacqueline A.; Tolchin, Benjamin; Dlugos, Dennis J.; Mikati, Mohamad A.; Harden, Cynthia
Abstract : Objective: To update a 1996 American Academy of Neurology practice parameter. Methods: The authors systematically reviewed literature published from January 1991 to March 2020. Results: The long-term (24–60 months) risk of seizure recurrence is possibly higher among adults who have been seizure-free for 2 years and taper antiseizure medications (ASMs) vs those who do not taper ASMs (15% vs 7% per the 1 Class I article addressing this issue). In pediatric patients, there is probably no significant difference in seizure recurrence between those who begin tapering ASMs after 2 years vs 4 years of seizure freedom, and there is insufficient evidence of significant difference in risk of seizure recurrence between those who taper ASMs after 18 months of seizure freedom and those tapering after 24 months. There is insufficient evidence that the rate of seizure recurrence with ASM withdrawal following epilepsy surgery after 1 year of seizure freedom vs after 4 years is not significantly different than maintaining patients on ASMs. An epileptiform EEG in pediatric patients increases the risk of seizure recurrence. ASM withdrawal possibly does not increase the risk of status epilepticus in adults. In seizure-free adults, ASM weaning possibly does not change quality of life. Withdrawal of ASMs at 25% every 10 days to 2 weeks is probably not significantly different from withdrawal at 25% every 2 months in children who are seizure-free in more than 4 years of follow-up. Recommendations: Fourteen recommendations were developed.